Penggunaan dan Analisis Modal Verbs Kunci (Should, Will, Would, Can, Could, May, Might, Must) dalam Bahasa Inggris - Muhlisin; Muhammad Ilham; Rahmadiyanti; As-Syifa Salsabila; Mila Erliana; Dewo Prasetiyo; Ahmad Rasyid (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to provide a comprehensive analysis of the nine key modal auxiliary verbs in the English language, as presented in the study titled "Usage and Analysis of Key Modal Verbs (Should, Will, Would, Can, Could, May, Might, Must) in English." The primary goal is to elucidate the diverse functions and subtle meanings of should, will, would, can, could, may, might, and must across various grammatical and communicative settings. The analysis meticulously explores their application in conveying concepts such as obligation (must, should), ability/possibility (can, could, may, might), volition/future time (will, would), and suggestions/requests (would, can, could). Furthermore, this study investigates the distinction between their root and epistemic uses, outlining common usage pitfalls and the syntactic rules governing their interaction with main verbs. This detailed examination is critical for English language learners and instructors striving for enhanced accuracy and communicative competence.